Inhibitory effect of the reversal agents V-104, GF120918 and Pluronic L61 on MDR1 Pgp-, MRP1- and MRP2-mediated transport - Evers, R (Nature Publishing Group, 2000)
The human multidrug transporter MDR1 P-glycoprotein and the multidrug resistance proteins MRP1 and MRP2 transport a range of cytotoxic drugs, resulting in multidrug resistance in tumour cells. To overcome this form of drug resistance in patients, several inhibitors (reversal agents) of these transporters have been isolated. Using polarized cell lines stably expressing human MDR1, MRP1 or MRP2 cDNA, and 2008 ovarian carcinoma cells stably expressing MRP1 cDNA, we have investigated in this study the specificity of the reversal agents V-104 (a pipecolinate derivative), GF120918 (an acridone carboxamide derivative also known as GG918), and Pluronic L61 (a (poly)oxypropethylene and (poly)oxypropylene block copolymer). Transport experiments with cytotoxic drugs with polarized cell lines indicate that all three compounds efficiently inhibit MDR1 Pgp. Furthermore, V-104 partially inhibits daunorubicin transport by MRP1 but not vinblastine transport by MRP2. V-104 reverses etoposide resistance of 2008/MRP1 cells, whereas GF120918 does not reverse resistance due to MRP1. V-104 partially inhibits the export of the organic anion dinitrophenyl S -glutathione by MDCKII-MRP1 but not by MDCKII-MRP2 cells. Unexpectedly, export of the organic anion calcein by MDCKII-MRP1 and MDCKII-MRP2 cells is stimulated by Pluronic L61, probably because it relieves the block on entry of calcein AM into the cell by endogenous MDR1 Pgp. © 2000 Cancer Research Campaign